Modulation of Ethanol Withdrawal–Induced Anxiety-Like Behavior During Later Withdrawals by Treatment of Early Withdrawals With Benzodiazepine/γ-Aminobutyric Acid Ligands - Knapp, Darin J. (2005)
BACKGROUND: Anxiety states, including those arising during acute or protracted withdrawal periods, may be precipitating factors in alcoholic relapse. Given the cyclical nature of ethanol withdrawal associated with repeated cycles of ethanol intake and abstinence in a pattern that often spans years, meaningful attempts to model ethanol withdrawal–associated anxiety should incorporate cycled ethanol treatments. The studies reported herein examined the effects of γ-aminobutyric acid–modulating drugs on social interaction behavior—an established model of anxiety—in rats exposed to repeated cycles of ethanol treatment and withdrawal. METHODS: Rats were exposed to 8 to 12 g/kg/day ethanol during three 7-day dietary cycles (5 days on ethanol diet followed by 2 days on control diet). Ethanol was administered either at hour 4 of withdrawal after cessation of each of the first 2 ethanol cycles or during the final withdrawal only. In other groups, the early withdrawals were treated with alphaxalone, diazepam, PK11159, or flumazenil to block anxiety-like behavior during an untreated later (third) withdrawal. The benzodiazepine inverse agonist DMCM (methyl–6, 7–dymerhoxy–4–ethyl–beta–carboline–3–carboxylate) was also given repeatedly to determine whether it would sensitize anxiety-like behavior during a future withdrawal. Finally, the effects of all drugs on deficits in locomotor behavior were assessed. RESULTS: Pretreatment of earlier withdrawals with alphaxalone, diazepam, ethanol, or flumazenil reduced social interaction deficits during a later withdrawal, but pretreatment with PK11195 did not. In contrast, DMCM administered in lieu of early withdrawals increased social interaction deficits during an untreated later withdrawal. Locomotor deficits were significantly reversed only by the acute ethanol and diazepam treatment during the final withdrawal. CONCLUSIONS: Single-dose administration of drugs that enhance or diminish activity at benzodiazepine–γ-aminobutyric acid- receptors during earlier withdrawals reduced or potentiated, respectively, anxiety-like behavior during later, drug-free withdrawals. These results support the potential of the novel strategy of using prophylactic therapy administered during early withdrawals to ameliorate symptoms of later withdrawals.